Accuracy And Precision of Anthropometric Measurements by Health Cadres: A Literature Review - Diyan, Diyan Tauhidah Romadhoni; Nia Novita Wirawan; Nurul Muslihah (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Anthropometric measurements, including height, weight, and body circumferences, are extensively utilized in healthcare to evaluate the development and growth of the body of individuals. However, the accuracy and precision of these measurements can be affected by the expertise and training of the individuals responsible for conducting the measurements. This literature review systematically examines the existing research on the accuracy and precision of anthropometric measurements performed by health cadres, who often serve as the primary assessors of nutritional status. A comprehensive literature search was performed utilizing multiple databases. From 10 relevant articles from PubMed and 40 from Scopus, A total of eleven articles met the inclusion requirements. The results showed that health workers and cadres differed in the accuracy and precision of body length measurements; R for nurses (92.3%) was higher in session B than R for cadres (87.5%). Importantly, measurement precision improved significantly after cadres received structured training and followed standardized protocols. These results emphasize the critical need for comprehensive training and standardized procedures to enhance anthropometric information collected by healthcare workers.